Using augmented reality to make school atlases more user-friendly for schoolchildren : Upotreba proširene stvarnosti kako bi školski atlasi bili učenicima što prihvatljiviji - Yonov, Nikola (Array, 2022)
Augmented reality (AR) technology allows cartographers to make cartographic products more attractive and more understandable for their users. In our research experiment we applied new AR technology onto a paper version school geography atlas for grade 8 (15-year-olds). The experiment that we did was carried out with grade 3 students (10-year-olds). The challenge we had was to see how small children would understand the complicated geographic information presented by the atlas using AR. The results show that students deal with the information and understand maps correctly with the help of the newly presented information. The children were very interested and asked to continue lessons. They were even interested in how the atlas was created using AR technology. It is evident that the presented new technology provides us with possibilities of explaining difficult geographic topics to students of different ages.